1987
DOI: 10.1063/1.98653
|View full text |Cite
|
Sign up to set email alerts
|

Co/Si(111) interface: Formation of an initial CoSi2 phase at room temperature

Abstract: Ultrathin films (≲50 monolayers) of Co have been deposited on atomically clean 7×7 Si(111) surfaces at room temperature and characterized by in situ surface techniques such as Auger electron spectroscopy and low-energy electron diffraction. Formation of a boundary CoSi2-like phase is surprisingly found at a very low coverage range (≲4 monolayers) as evidenced by low-temperature transport measurements (resistivity and Hall effect) and also by cross-sectional high-resolution transmission electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…CoSi (the heat of formation, DH f = À12 kcal/g atoms), Co 2 Si (DH f = À9 kcal/g atoms) and CoSi 2 (DH f = À8.2 kcal/g atoms). It was found that in thermal annealing, Co 2 Si is the first phase to form and Co is the dominant moving species in the formation of Co 2 Si, in agreement with previous results [28]. In ion beam mixing, both CoSi and Co 2 Si phases have been observed to form [13,14].…”
Section: Resultssupporting
confidence: 82%
“…CoSi (the heat of formation, DH f = À12 kcal/g atoms), Co 2 Si (DH f = À9 kcal/g atoms) and CoSi 2 (DH f = À8.2 kcal/g atoms). It was found that in thermal annealing, Co 2 Si is the first phase to form and Co is the dominant moving species in the formation of Co 2 Si, in agreement with previous results [28]. In ion beam mixing, both CoSi and Co 2 Si phases have been observed to form [13,14].…”
Section: Resultssupporting
confidence: 82%
“…A 2% magnetocurrent was observed in the original experiment [150]. By relocating the ferromagnetic bases away from silicon interfaces to eliminate the ''magnetically-dead'' silicide layer [1074][1075][1076], the magnitude of magnetocurrent was substantially increased by more than one order of magnitude [280,1049]. To further confirm that the change in I c2 is indeed caused by the spin valve effect instead of other spurious effects, non-local spin detection was also used [281].…”
Section: Spin Transport In Siliconmentioning
confidence: 84%
“…CoSi 2 . 17 In the present study, the partial ordering of the film structures may be attributed to the relatively low temperature of the Ge(111) substrate. According to the EHF model, improved crystallinity would be expected with a Ge(111) substrate at higher temperatures.…”
Section: Discussionmentioning
confidence: 95%